Effects of sildenafil on right ventricle remodelling in Portopulmonary hypertension. (October 2021) - Rossi, Rosario; Talarico, Marisa; Schepis, Filippo; Coppi, Francesca; Sgura, Fabio Alfredo; Monopoli, Daniel Enrique; Minici, Roberto; Boriani, Giuseppe
Abstract: Portopulmonary hypertension (PoPH) is a clinical condition associated with end‐stage liver disease, described by the coexistence of pulmonary arterial hypertension (PAH) and portal hypertension. In PoPH patients, there is a right ventricle (RV) remodeling to compensate for the increased resistance in the lung circulation. There are no studies on the effects of the PAH-targeted pharmacological treatment on the RV dimension and function. The present study summarizes our experience in patients with PoPH treated with sildenafil in a period of 6 years (from 2013 to 2019). We enrolled 64 consecutive patients identified as PoPH, all treated with sildenafil (57.6% in monotherapy; in the other cases in association with macitentan; in 19.0% with initial combination therapy). A hemodynamic invasive cardiopulmonary study was performed at baseline and after 6 months of sildenafil treatment. In our population we showed a significative improvement in RV performance, with a significant increase in RV stroke volume (+33%), RV ejection fraction (+31%) and RV stroke work index (+17.5%). We registered the reduction of the RV cavity dimension over time in all patients treated with sildenafil (RV end diastolic diameter decreased by 15% after 6 months of follow-up). Regarding diastolic function, we highlighted a very significant reduction in RV end-diastolic pressure (−50% concerning baseline). Sildenafil was effective both when used as monotherapy and in combination with macitentan. In conclusion, Sildenafil had a positive impact on RV systolic and diastolic function in patients with PoPH and was able to conditionate the reverse remodeling of the RV. Highlights: In chirrosis 2-6% patients shows porto-pulmonary hypertension. Right ventricle function is a prognosist determinant in pulmonary hypertension. Sildenafil is used in this condition because free from hepatotoxicity. Sildenafil alone or with Macitentan improved right ventricle function and hemodynamics.